Various Artists : the best of. - Bompuis, Catherine; Meireles, Cildo (São Paulo : Galeria Luisa Strina, 2012)
Turing, Armin ; Roselare, Innumerat ; Leroy, Bernard ; Korstjens, Johannes ; Drib, Lima ; n.e.b.u.s.i. ; Digi_Shelf, Sheehy, Délia ; Depoortere, Willy ; Thensiau, Aude ; Coppens, Christl ; Martaque, Al Khawarizm, Jamila ; Zooeydottir, Steina ; Engels, Trudo ; Da Silva, Valereson ; Eraser, Omandichana, Ana ; Janssens, Cindy ; Grant, Freddy ; Coppens, Martn ; Ingelbreč, Robert ; Dewaere, Diederick ; Marcella.B. ; de Lisle, Morice ; Sufferice, Savereys, Albert ; Aude Thensiau, Hélène
boek